Depression in young women after hysterectomy: Emergency obstetric versus elective procedure – A comparative cross-sectional study - Brohi, Zahida Parveen; Uzma Parveen; Ujjan, Roohi; Brohi, Aneela; Mahesar, Afshan (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Emergency obstetric hysterectomy (EOH) is done during cesarean section or after normal vaginal delivery, or any time during puerperal period. Puerperal period is usually associated with anxiety and depression in most cases, having emergency hysterectomy can potentially trigger it more. Therefore, this study was conducted to compare emergency versus elective hysterectomy to determine the pattern of depression between two groups. During a period of four years (from 1st march 2019 to 28th February 2023), a total of 6658 patients were admitted in obstetrics & gynecology department and 31 underwent emergency obstetric hysterectomies and consented to be part of this study. These females were aged between 18 to 49 years. For comparison 31 married control females were randomly selected and interviewed 3 months after undergoing elective hysterectomy due to gynecological conditions. There was no past family history for any psychiatric illness in both groups. The studied groups were clinically evaluated for major depressive episode according to the American Psychiatric Association diagnostic and statistical Manual of mental disorders, 4th edition text revised (DSM-IV TR) criteria. Beck depression inventory (BDI)18 to assess the severity of major depressive episodes. Out of 31 patients 16 cases were performed after caesarean section, four during laparotomy for ruptured uterus and 11 for uterine atony after normal vaginal delivery. There was significantly higher rate of depression among patients undergoing emergency hysterectomy as compared to those with elective procedure. The frequency of complications was also observed to be higher in emergency cases. Our study concluded that the frequency of complications and severe depression was remarkably higher in the obstetric emergency hysterectomy group as compared to the elective hysterectomy group.